2020
DOI: 10.3389/fmolb.2020.00032
|View full text |Cite
|
Sign up to set email alerts
|

FAIM Is a Non-redundant Defender of Cellular Viability in the Face of Heat and Oxidative Stress and Interferes With Accumulation of Stress-Induced Protein Aggregates

Abstract: A key element of cellular homeostasis lies in the way in which misfolded and dysfunctional proteins are handled. Cellular pathways that include proteasomal destruction and autophagic disposal are components of normal proteostasis. Here we report a novel molecule that plays a non-redundant role in maintaining homeostasis, Fas Apoptosis Inhibitory Molecule (FAIM). FAIM is highly conserved throughout evolution and bears no homology to any other protein. We found that FAIM counteracts heat and oxidative stress-ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…We previously showed ubiquitinated protein aggregates induced by cellular stress and mutant SOD1 aggregates accumulate in FAIM-deficient cells ( Kaku et al, 2020 ; Kaku and Rothstein, 2020 ). To assess the role FAIM plays in prevention of Aβ aggregation, we employed an APP-overexpression system using Neuro 2A cells, a mouse neuroblastoma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed ubiquitinated protein aggregates induced by cellular stress and mutant SOD1 aggregates accumulate in FAIM-deficient cells ( Kaku et al, 2020 ; Kaku and Rothstein, 2020 ). To assess the role FAIM plays in prevention of Aβ aggregation, we employed an APP-overexpression system using Neuro 2A cells, a mouse neuroblastoma.…”
Section: Resultsmentioning
confidence: 99%
“…Given that FAIM protein prevented and solubilized Aβ fibrils, we suggest the novel hypothesis that low/no FAIM expression might be pathogenically linked to more rapid, aggressive, overwhelming Aβ fibrillization in AD patients rather than simply functioning as a marker of AD progression. Furthermore, we previously showed that oxidative stress, applied in vivo to intact animals, produces increased protein aggregates in FAIM-deficient mice ( Kaku and Rothstein, 2020 ). Previous reports suggest that oxidative stress is linked to neurodegenerative diseases, presumably due to accumulation of toxic protein aggregates triggered by protein oxidation ( Butterfield and Kanski, 2001 ; Chong et al, 2005 ; Chen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, FAIM (Fas apoptosis inhibitory molecule) was first identified as a negative regulator of Fas signaling ( Schneider et al, 1999 ). It was later found to play multifaceted roles in other physiological processes such as the protective or deleterious effects of TNFα in neurodegenerative disorders ( Carriba et al, 2015 ), regulating axon-selective pruning, hippocampal long-term depression (LTD) ( Martinez-Marmol et al, 2016 ) and opposition to stress-induced accumulation of protein aggregates ( Kaku and Rothstein, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Parkinson’s disease, the expression of FAIM-L was found to be reduced in midbrain dopaminergic neurons after trophic factor deprivation, as well as to sensitize them to Fas-induced cell death ( Yu et al, 2008 ). Recent findings also show that FAIM could play a role in Amyotrophic Lateral Sclerosis inhibiting the aggregation of mutant SOD1, suggesting that FAIM participates in maintaining cell homeostasis ( Kaku and Rothstein, 2020 ). Kaku et al (2020) also described that FAIM is recruited to cellular stress-induced ubiquitinated proteins, and the levels of stress-induced protein aggregates are much greater in FAIM-deficient cell lines.…”
Section: Introductionmentioning
confidence: 99%